Prevalence of and risk factors for adolescent scoliosis from a multi-year school screening programme in Eastern China - Xu, Rong; Li, Jianghui; Wang, Weihong; Zhang, Lijun; Liu, Hua (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to determine the occurrence of adolescent scoliosis (AS) and identify possible associated factors in Eastern China.MethodsThe screening technique involved performing forward bending tests and using scoliometer data. Adolescents at risk for scoliosis based on the screening were advised to undergo an x-ray examination for diagnosis confirmation.ResultsBetween 2019 and 2023, a total of 90,635 adolescents, comprising 41,836 females and 48,799 males, aged 11–18, underwent screening. Among the screened adolescents in Eastern China, the overall prevalence of scoliosis was 0.62%, with 0.99% in females and 0.30% in males. Independently associated factors were identified as female gender (OR = 1.319, 95% CI 1.031–1.686, P = 0.027), BMI ≤ 20 (OR = 2.959, 95% CI 2.271–3.855, P < 0.001), a tendency to incline towards one side (OR = 2.129, 95% CI 1.564–2.898, P < 0.001), and a habit of bending over the desk (OR = 1.523, 95% CI 1.079–2.150, P = 0.017).ConclusionThe current study found that the occurrence rate of AS in Eastern China is 0.62%. Female adolescents who are thin and tall and have poor learning posture are more susceptible to developing scoliosis.